The Relevance of Explanatory First-Person Approaches (EFPA) for Understanding Psychopathological Phenomena. The Role of Phenomenology - Schmidt, Philipp (Frontiers in Psychology, 2018)
The main aim of this paper is to demonstrate the contributions of phenomenology-inspired approaches to the explanation of psychopathological phenomena. First, I introduce the notion of Explanatory First-Person Approaches (EFPA) which share the assumption that the explanation of consciousness and conscious phenomena necessitates, at least partially, phenomenal facts functioning as explanans. Phenomenal facts refer to facts about structures and processes of consciousness. To differentiate phenomenology from other EFPA and to extract its distinctive feature, I compare phenomenology to the method falling under the category of EFPA it overlaps with the most: new introspective methods as recently described. I then present genetic phenomenology as the distinctive feature of phenomenology and show how particularly genetic phenomenology complements biological explanations of psychopathological phenomena in the context of psychiatric disorders such as schizophrenia. Moreover, I present Cognitive Theory (CT) as the most acknowledged EFPA in the broader scientific community, demonstrate CT’s limitations in explaining conscious phenomena in the context of psychological disturbances such as depression, and show how genetic phenomenology can also significantly complement the cognitive approach. An example in the context of burnout-depression will be given. The overall argument for the significance of phenomenology is as follows: Genetic phenomenology renders phenomenology a distinctive kind of EFPA; genetic phenomenology can complement one of the most dominant non-EFPA accounts in the science of psychiatric disorders: biological reductionism; and genetic phenomenology can complement the most dominant existing EFPA in the science of psychological disturbances: Cognitive Theory.